Documentos del Cuzco: historia y poder - Trelles, Efraín (1980)
Under the suggestive title of Cuzco: Waters and Power, the Center for Andean Rural Studies "Bartolomé de las Casas" has brought to light number 1 of a promising series: Archivos de Historia Rural Andina. In this case, we are dealing with the publication, in a neat paleographic version by Horacio Villanueva and Jeannette Sherbondy, of six sets of documents related to the waters and lands of Cuzco, whose time span ranges from the end of the 16th century to just under the middle of the 19th century. Nothing less.